Engineering in emergencies : - Davis, Jan. (ITDG, 1997)
A practical handbook for engineers and relief workers providing humanitarian assistance. Basic practical information is provided to implement an effective engineering response in the aftermath of an emergency. The focus of the book is the type of emergency typified by the Rwandan crisis and the ensuing refugee exodus to Tanzania and Zaire, but it is relevant to a broad range of emergencies and disasters. It has been prepared on behalf of Red R (Registered Engineers for Disaster Relief). Red R selects, prepares and supplies engineers and technicians to front-line relief agencies. The contents of the book reflect both the field experience of these relief workers and the experience that Red R has accumulated through training and debriefing. The book deals in depth with "hard" subjects (water, sanitation, roads and shelter). There is also an emphasis on the "soft" subjects needed for effective relief work (managerial skills, personal effectiveness, an appreciation of the needs of refugees and the international relief system).